Effects of Wide Single Tyres and Dual Tyres – A Technical and Economic Approach – Report on Cost 334 - Faber, A.; Hahn, W.D. (Engineering Transactions, 2000)
This paper deals with the comparison of technical and economic aspects for heavy commercial vehicles fitted with wide base single or dual tyres (Fig. 1). The task is a part of the European research project "COST 334: Effects of Wide Base Single Tyres and Dual Tyres" which includes pavement wear effects, vehicle operational and pavement maintenance cost models, non–pavement effects and the consequences. The paper presented here describes mainly the problems of driving behaviour and vehicle safety.